The Effect of Environmental Performance, Environmental Costs and Environmentally Friendly Products on Financial Performance - Febyanti Dwi AMANDA; Slamet WIYONO; Titik ARYATI (PT Keberlanjutan Strategis Indonesia, 2025)
This research aims to find out whether environmental performance, environmental cost and eco-friendly products influence the financial performance of manufacturing companies on the Indonesia Stock Exchange. This type of company was chosen because the company has a high level of sensitivity which is of concern to investors due to the large amount of energy expended for its operational activities. The population used is cement, chemical and mining industry companies listed on the Indonesia Stock Exchange in 2021-2023. Sample selection was used through a purposive sampling method, during the 2021-2023 observation period and was not delisted during the research period, resulting in a total sample of 120 samples. Based on the testing of 120 samples, tests were then carried out including descriptive statistics, classical assumption tests and research hypothesis tests. The results of the hypothesis test are that environmental performance has a positive effect on the company's financial performance, environmental costs have a positive effect on the company's financial performance, and environmentally friendly products have a positive effect on the company's financial performance.